(untitled) (International Journal of Engineering and Computer Science, 2017)
The modeling and performance analysis of BLDC motor under different operating speed conditions has been presented in this paper. BLDC motors have been gaining attention from various Industrial and household appliance manufacturers, because of its high efficiency, high power density, and low maintenance cost. After many research and developments in the fields of magnetic materials and power electronics, their applications to electric drives have increased to a significant extent. In this paper, the modeling of Brushless DC motor drive system along with control system for speed and current has been presented using MATLAB / SIMULINK. In order to evaluate the model, various cases of simulation studies are carried out. Test results thus obtained show that the model performance is satisfactory.